Anti-cancer actions in commonly used drugs: epidemiology led by laboratory science - Walker, Alex J. (2011)
Despite considerable research on cancer treatments and preventatives, poor outcomes in cancer patients are common. The vital search for effective cancer drugs often begins in the laboratory, where unfortunately the effects of a drug in humans cannot be perfectly modelled. Epidemiology can play a vital role in determining the real world efficacy of a drug currently used for other purposes before clinical trials begin. This thesis therefore used primarily laboratory evidence to identify potential anti-cancer uses for existing common drugs. The drugs and cancers studied were; tricyclic antidepressants and both incidence and survival in a number of cancer types, particularly glioma; aspirin and colorectal cancer survival; and angiotensin converting enzyme (ACE) inhibitors and hepatocellular carcinoma (HCC) incidence.